2012
DOI: 10.1111/cup.12033
|View full text |Cite
|
Sign up to set email alerts
|

Basal cell carcinoma of the skin: whole genome screening by comparative genome hybridization revisited

Abstract: Basal cell carcinoma (BCC) of the skin is considered to be the most common malignancy in people of European ancestry. It is often not clinically aggressive and has been regarded as genetically stable. However, histopathologic subtypes of BCC differ in their ability to invade surrounding tissues and recur. The aim of this work was to present a comprehensive study of chromosomal imbalances of cutaneous BCC and to correlate the findings with their histopathologic and clinical features. In all, 101 tumor samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
1
10
1
Order By: Relevance
“…This alteration has not been observed previously in untreated BCCs (Pesz et al, 2013) and therefore might only provide a selective advantage in the presence of a SMO inhibitor. Strikingly, both copies of PTEN were lost in one case, suggesting this may not be a passenger CNV.…”
Section: Discussionsupporting
confidence: 45%
“…This alteration has not been observed previously in untreated BCCs (Pesz et al, 2013) and therefore might only provide a selective advantage in the presence of a SMO inhibitor. Strikingly, both copies of PTEN were lost in one case, suggesting this may not be a passenger CNV.…”
Section: Discussionsupporting
confidence: 45%
“…Trisomy 6 was only observed in two (15.4 %) of our samples, whereas the frequency varied from 19 % to 38 % in other studies [5][6][7] . In our series, gains of the region 6p21.1 were detected in 54 % of BCC cases, a rate similar to the 47 % previously reported for the region 6pter-p21 [ 4 ] .…”
Section: Case Nocontrasting
confidence: 68%
“…Histological subtype Sun exposed area * Age/Gender Aneuploidies To our knowledge, there have been two reports of chromosomal imbalances in cases of BCC using array-CGH [ 4,5 ] , but no regions of chromosomal gains or losses have been specifi ed. These two studies and our series confi rm the presence of aneuploidies in BCC samples.…”
Section: Case Nomentioning
confidence: 99%
“…Characteristic CNV have been identified in other UV-induced skin tumors such as malignant melanomas [ 3 ], cutaneous SCC [ 4 ] and BCC [ 5 ]. In only one previous study comparative genomic hybridization (CGH) revealed many shared CNVs in AFX and PDS (most frequently deletions on chromosomes 9p and 13q).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to somatic mutations, copy number variations (CNV) by gain of specific chromosomal segments containing relevant oncogenes or loss of chromosomal segments harboring critical tumor suppressor genes have been shown to be highly characteristic of other UV-induced skin tumors such as malignant melanoma [ 3 ], cutaneous squamous cell carcinoma (SCC) [ 4 ] and basal cell carcinoma (BCC) [ 5 ]. The aim of the present study was to analyze CNV in a large sample cohort of AFX and PDS to get further insights into their evolutionary process as well as to detect additional diagnostic or therapeutic target structures.…”
Section: Introductionmentioning
confidence: 99%